Aerodynamic Performance of an Adaptive Rear Wing at Different Angles of Attack - Kolcu, Boran Beyit (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2022)
In this paper, computational fluid dynamics results are presented on an active rear wing designed based on the S1223 aerofoil profile. The rear wing was subjected to turbulent flow with the standard two equation k-ε turbulence model, using ANSYS Fluent software to study the aerodynamic behaviour and the force generating capabilities of the wing. The simulation was performed when the wing was set at four different angles of attack. Flow visualisation was performed to understand the nature of the air flow around the wing. Force components were additionally calculated for downforce and drag force comparison at different angles of attack, a maximum of 190.828 N and a minimum of 121.891 N of downforce was calculated. Drag force was 12.895 N at its minimum and a highest drag force of 19.518 N was calculated. It was found out that the S1223 aerofoil profile successfully aided the rear wing to generate downforce at relatively low angles of attack.

ÖZ: Bu çalışmada, S1223 hava folyosu profiline sahip bir aktif arka kanat’ın hesaplamalı akışkanlar dinamiği sonuçlarına yer verilmiştir. Arka kanat k-ε türbülans modeli kullanılarak türbülanslı akışa tabi tutulmuştur. Arka kanat dört farklı hücum açısı kullanılarak simülasyona tabi tutulmuştur, Arka kanat etrafından akan havanın doğasını anlayabilmek için akış görselleştirme kullanılmıştır. Ayrıca, farklı hücum açılarındaki yere basma kuvveti ve sürüklenme kuvvetlerini karşılastırmak için farklı kuvvet öğeleri hesaplanmıştır, maksimum 190.828 N ve minimum 121.891 N bastırma kuvveti hesaplandı. Sürükleme kuvveti minimumda 12.895 N ve maximumda 19.518 N olarak hesaplandı Çalışmanın sonucunda, S1223 hava folyosu profilinin arka kanat’ın düşük hücum açılarında yere basma kuvveti üretiminde faydalı olduğu ortaya çıkmıştır.
Master of Science in Mechanical Engineering. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Engineering, Dept. of Mechanical Engineering, 2022. Supervisor: Prof. Dr. Hasan Hacışevki.
Keywords: Mechanical Engineering; Automobiles--Aerodynamics; Fluid Dynamics; Motor vehicles--Design and construction; Automotive aerodynamics, downforce, computational fluid dynamics